Camrelizumab-Related Myocarditis and Myositis With Myasthenia Gravis: A Case Report and Literature Review - Bai, Jing; Li, Dan; Yang, Peidan; Xu, Kunyan; Wang, Yingnan; Li, Qian; Liu, Jiang; Du, Wenli; Zhang, Fengbin; Feng, Rui (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs) have substantially changed the treatment of a variety of malignant tumors. With the increasing of their usage, the unique immune-mediated toxicity profile of ICIs has become apparent. We report a case of esophageal squamous cell carcinoma in a patient who received anti-programmed cell death protein 1 (PD-1) (camrelizumab) therapy and the occurrence of sequential immune-related adverse events (irAEs). Although many irAEs have been reported, severe myositis caused by camrelizumab with simultaneous involvement of multiple organs, including the myocardium, respiratory muscles, and skeletal muscles, has rarely been described in literature. This 69-year-old male patient developed a grade 4 camrelizumab-induced adverse reaction according to the Common Terminology Criteria for Adverse Events (CTCAE) and was successfully treated with methylprednisolone and immunoglobulins. The early identification of irAEs, immediate discontinuation of immunotherapy, use of steroids and/or immunosuppressants, and adjuvant supportive treatment are critical to the clinical prognosis of patients. It should be aware that autoimmune complications can occur even when ICI treatment is ceased.